2021
DOI: 10.1177/23409444211035138
|View full text |Cite
|
Sign up to set email alerts
|

Building resilience and performance in turbulent times: The influence of shared leadership and passion at work across levels

Abstract: The COVID-19 pandemic has tested health care professionals to the extreme. This study investigated the re-enchanting effect of shared leadership and passion at work in the context of public health care. This study advances on the Self-Determination Theory to suggest that shared leadership has a positive effect on resilience and performance through passion at work at different levels of analysis. A sample of 518 physicians working in Spanish public hospitals was used. The results showed that shared leadership w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 96 publications
1
28
0
Order By: Relevance
“…In addition, the findings presented in this special issue (e.g., Griep et al, 2021;Salas-Vallina et al, 2021;Sarmah et al, 2021) suggest that the factors that are relevant for the study of re-enchantment may be found at different (organizational-, team-, individual-) yet related levels of analysis. Therefore, to fully understand workplace re-enchantment one should account for the multilevel nature of the phenomenon (Xanthopoulou & Bakker, 2021).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, the findings presented in this special issue (e.g., Griep et al, 2021;Salas-Vallina et al, 2021;Sarmah et al, 2021) suggest that the factors that are relevant for the study of re-enchantment may be found at different (organizational-, team-, individual-) yet related levels of analysis. Therefore, to fully understand workplace re-enchantment one should account for the multilevel nature of the phenomenon (Xanthopoulou & Bakker, 2021).…”
Section: Discussionmentioning
confidence: 91%
“…Namely, to understand what makes enchanted workplaces and how, as well as what it means to feel enchanted and how this state may be achieved by individuals. As concerns the former issue, the studies included in this special issue mainly focus on leadership and highlight how different leadership styles (e.g., servant or autonomous supportive leadership; Kaltiainen & Hakanen, 2020;Sarmah et al, 2021) or ways that leadership may be executed or shared (Salas-Vallina et al, 2021) may facilitate workplace enchantment. With regard to the latter, the studies of Griep et al and Pessi et al emphasize how intra-individual and inter-individual emotional experiences motivate employees to engage in behaviors that may not only help them make their own work more meaningful but also the work of others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high level of consuming passion may be necessary to manage the rigors and expectations of this high stakes profession. Indeed, other work measuring the impact of passion among healthcare teams has shown that passion can boost physician’s energy to tackle challenging circumstances and recover successfully from them, thereby boosting individual performance [ 12 ]. For a specialty that often provides the advice of, “If you can see yourself doing anything other than surgery, than do the other thing,” these findings may be especially helpful.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of shared leadership has historical roots; almost a century ago, Follett suggested in 1924 that one should look not only to the designated leader but also to others on the team for leadership (D'Innocenzo et al 2021). Then, Gibb introduced this form of leadership in 1954 (Salas-Vallina et al 2022). Researchers have explained this leadership with different definitions and conceptualizations (Klasmeier and Rowold 2022).…”
Section: Lss and Iepmentioning
confidence: 99%